Studies on the Growth and Development of Root-Knot Nematode Meloidogyne incognita of Phaseolus vulgaris in Tissue Culture Media - Monaim MF, Abdel (Open Access Journal of Mycology & Mycological Sciences, 2023)
The study was conducted to study the growth and development of root-knot nematode, Meloidogyne incognita of Phaseolus vulgaris in tissue culture media. The data revealed the developmental common bean cv. Paulista of M.S media as the following: the seed swelling stage after three days, the radical appearance stage after five days. The cotyledons leaves appear after six days, the cotyledon leaves appear after eight days, and the seedling stage after twelve days. The life cycle of M. incognita completed about thirty-seven days in root tissues of Paulista cultivar. Microscopic examinations of the infected bean roots revealed the following: Second-stage juveniles of M. incognita penetrated the roots within 24 hrs after nematode inoculation. Third-stage juveniles were observed in roots (six-eight) days after nematode inoculation. While, fourth stage juveniles were observed in roots 12-14 days after nematode inoculation. The pre-adult females were seen inside roots within twenty days after nematode inoculation. The adult females were seen inside roots within twenty-seven days after nematode inoculation. Egg laying females with deposit egg masses of M. incognita was observed thirty-seven days after nematode inoculation.